PHILOSOPHICAL PROBLEMS OF LEGAL ETHICS - Dilorom Ibrakhimova (Scholar Express Journals, 2024)
This article examines the philosophical underpinnings of legal ethics, exploring the fundamental dilemmas that challenge legal practitioners. It analyses how legal ethics intersects with broader moral philosophy, raising critical questions about the nature of justice, the role of the lawyer, and the tension between personal morality and professional duties. The discussion delves into key issues such as the conflict between zealous advocacy and moral responsibility, the challenge of maintaining confidentiality versus serving the public interest, and the ethical implications of modern technological advancements in the legal field.
Keywords: legal ethics; confidentiality; maintaining